Mimicking the surface and prebiotic chemistry of early Earth using flow chemistry - Dougal J. Ritson (Nature Portfolio, 2018)
There is still much debate on early Earth geochemical conditions affecting the chemistry of simple synthons that originated life. Here, the authors report an uninterrupted multistep synthetic route to 2-aminooxazole by means of flow chemistry equipment, mimicking a plausible early Earth (geo)chemical scenario.